2022
DOI: 10.1111/are.15932
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofMoringa oleifera‐based diets on growth, immunological responses, liver antioxidant biomarkers and expression of immune‐related genes in Nile tilapia (Oreochromis niloticus) raised in hapa‐in‐pond system

Abstract: We have evaluated the impacts of supplementing diets with Moringa oleifera leaf extract (MOL) on growth, intestine histomorphometry, immunity, liver antioxidants and expression of immune genes in Nile tilapia raised in hapas mounted in earthen pond. Four MOL supplementation doses (0.0, 5.0, 7.0 and 9.0 g/kg) were used to make four experimental diets defined as reference (CONT), MOL5, MOL7 and MOL9 respectively. Fish (⁓61.5 g) were allocated in 4 triplicate groups and were fed the corresponding diets for consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 92 publications
2
6
0
Order By: Relevance
“…The leaves are also abundant in several essential vitamins, minerals (like potassium, iron, and calcium) 9 , and phytochemicals (like carotenoids, flavonoids, phenolics, alkaloids, and terpenoids 10 . Due to the above-mentioned nutritive values, studies elucidated that MO-based meals could be proficiently consumed by poultry 11 , goats, cattle 12 , 13 , and fish 14 , 15 . The presence of anti-nutrient (anti-nutritional) factors may hinder the digestibility of MO-based diets, and in this case, it requires several processing techniques 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The leaves are also abundant in several essential vitamins, minerals (like potassium, iron, and calcium) 9 , and phytochemicals (like carotenoids, flavonoids, phenolics, alkaloids, and terpenoids 10 . Due to the above-mentioned nutritive values, studies elucidated that MO-based meals could be proficiently consumed by poultry 11 , goats, cattle 12 , 13 , and fish 14 , 15 . The presence of anti-nutrient (anti-nutritional) factors may hinder the digestibility of MO-based diets, and in this case, it requires several processing techniques 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The growth (FW, WG, and SGR) and feed utilization (FCR and PER) performance of Nile tilapia were significantly higher in the diet supplemented with the MLE-0.5 group. Similarly, the diet supplemented with M. oleifera leaf extract at 5 g [ 25 ] and seed extract at 0.5% [ 45 ] observed significantly higher growth indices of Nile tilapia. This phenomenon can be ascribed to the presence of bioactive compounds in MLE, namely p -coumaric acid, quercetin, and kaempferol.…”
Section: Discussionmentioning
confidence: 99%
“…Moringa exhibits anticancer, antidiabetic, anti-inflammatory, antioxidant, antifungal, and antibacterial properties attributed to the presence of bioactive compounds such as phenolic acid and flavonoids [ 15 , 16 , 17 , 18 ]. Moringa leaf extract has been employed in various studies to promote the growth, immune response, antioxidant activity, and disease protection of Nile tilapia at different life stages, including fry [ 19 , 20 , 21 ], fingerling [ 22 , 23 ], and adult [ 24 , 25 ] Nile tilapia. Additionally, a few studies have demonstrated the potential of Moringa leaf for reducing stress indices [ 20 , 24 ], as well as mitigating the sub-lethal toxicity of fipronil [ 26 ] and sub-chronic sodium fluoride [ 27 ] to Nile tilapia.…”
Section: Introductionmentioning
confidence: 99%
“…Discussion There is no doubt that the continuous water change improves the performance and wellbeing of the fish reflecting a positive effect on the parameters of growth, feed efficiency, and hematological, immunological, and histological indicators (Abdel-Latif et al, 2022;El-Son et al, 2022). A. vera is one of the candidate medicinal plants in the aquaculture feed industry as a feed supplement.…”
Section: % (Cfe) [I and J]mentioning
confidence: 99%